Inequality Overhang - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2017)
The linearity of the relationship between income inequality and economic development has been long questioned. While theory provides arguments for which the shape of relationship may be positive for low levels of inequality and negative for high ones, most of the empirical literature assumes a linear specification finding conflicting results. Employing an innovative empirical approach robust to endogeneity, we find pervasive evidence of nonlinearities. In particular, similar to the debt overhang literature, we identify an inequality overhang level in that the slope of the relationship between income inequality and economic development switches from positive to negative at a net Gini of about 27 percent. We also find that in an environment characterized by widespread financial inclusion and high income concentration, rising income inequality has a larger negative impact on economic development because banks may curtail credit to customers at the lower end of the income distribution. On the positive side, a sufficiently high female labor participation can act as a shock absorber reducing such negative impact, possibly through a more efficient allocation of resources.